2006
DOI: 10.1038/sj.cgt.7701010
|View full text |Cite
|
Sign up to set email alerts
|

Human adenovirus type 35 vector for gene therapy of brain cancer: improved transduction and bypass of pre-existing anti-vector immunity in cancer patients

Abstract: Clinical trials in malignant glioma have demonstrated excellent safety of recombinant adenovirus type 5 (Ad5) but lack of convincing efficacy. The overall low expression levels of the Coxsackie and Adenovirus receptor and the presence of high anti-Ad5-neutralizing antibody (NAb) titers in the human population are considered detrimental for consistency of clinical results. To identify an adenoviral vector better suited to infect primary glioma cells, we tested a library of fiber-chimeric Ad5-based adenoviral ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The differences in adenovirus transduction efficiency and promoter studies emphasize the importance to use short-term cultures of glioblastoma cells. In the meantime, Brouwer et al have demonstrated that recombinant Ad5/35 has a significantly higher transduction efficiency of primary glioblastoma cells than Ad5 [53]. However, the authors did not analyze the effects on treatment efficacy.…”
Section: Introductionmentioning
confidence: 91%
“…The differences in adenovirus transduction efficiency and promoter studies emphasize the importance to use short-term cultures of glioblastoma cells. In the meantime, Brouwer et al have demonstrated that recombinant Ad5/35 has a significantly higher transduction efficiency of primary glioblastoma cells than Ad5 [53]. However, the authors did not analyze the effects on treatment efficacy.…”
Section: Introductionmentioning
confidence: 91%
“…22 Ad35, a chimeric vector was found to have lower antigenic properties, but increased ability to transfer a gene to primary glioma cells compared with Ad5 depicting it as an interesting candidate vector for gene therapy of malignant glioma. 23 However, although genetic strategies to circumvent Coxsackie-adenovirus receptor deficiency in glioma cells could reproducibly expand the cellular entry mechanisms of Ad vectors in cultured and primary glioma cells, these approaches were insufficient to confer in vivo significant infectivity enhancement over unmodified Ad vectors, suggesting that other factors, such as extracellular matrix, stromal cells and the three-dimensional tumor architecture, have important roles in vivo and interfere with Ad-based gene delivery into gliomas. 24 Invasive tumors, including gliomas, utilize proteinases to degrade extracellular matrix components and diffuse into the adjacent tissues or migrate toward distant ones.…”
Section: Adenovirus Retrovirusmentioning
confidence: 99%
“…35 A conditionally replication-competent Ad5-based vector with the Ad35 fiber shaft and knob domains (Ad5/35) had a potent antiglioma effect suggesting that Ad35-based vectors may be useful for the treatment of glioma. 36 A replication-selective adenovirus (CB1) having a double deletion of the 24 bp Rb-binding region in the E1a gene, and a 903 bp deleted region in the E1b gene that abrogates the expression of the p53-binding E1B-55 kDa protein, exerted a potent anticancer effect in vitro in U-251 MG, U-373 MG and D-54 MG human glioma cell lines. In vivo experiments using intracranially implanted D-54 MG glioma xenografts improved survival of nude mice.…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…67 Examples include an Ad3 fiber knob (binds to CD80, CD86, and unknown receptor) and Ad5 fiber chimera (Ad5/3), which had greatly increased glioma infectivity and cytotoxicity in vitro 68,69 ; Ad5 with canine Ad1 (CK1) or porcine Ad (PK) fiber was more efficient than Ad5/3 70 ; and Ad16p (binds to CD46) and chimpanzee CV23 efficiently infected GSCs. 71 A screen of 16 Ad5 fiber chimeras on primary glioma cell cultures identified B-group viruses (Ad11, Ad35, Ad50 [bind to CD46, overexpressed in GBM]) as having greatly increased infectivity compared with Ad5, 72 with Ad5/35 extending survival in vivo. 68 These same strategies can be used for targeting replication-defective Ad vectors.…”
Section: Adenovirusesmentioning
confidence: 99%